John Crittenden Watson papers - Watson, John Crittenden, 1842-1923.; Watson, Edward H. (Edward Howe), 1873-1942.; Watson, James T.
General and family correspondence, reports, official orders, notes, newspaper clippings, photographs, scrapbooks, and other papers relating to Watson's naval career. Documents his Civil War service at Fort Jackson, Fort Saint Philip, and Chalmette, La., resulting in the capture of New Orleans, La., 1862; at Vicksburg, Miss., 1862; and at the Battle of Mobile Bay, La., 1864. Also documents his postwar duty as commander of the USS Wyoming (Sloop of war) with the U.S. Navy European Station; as commander of the U.S. Navy Asiatic Squadron; as American naval representative at the coronation of Edward VII, King of Great Britain; and the controversy with U.S. secretary of the navy William E. Chandler over the dismissal of civilian employees at the New York Naval Shipyard in 1883. Includes papers of Watson's sons, U.S. naval officer Edward H. Watson, relating to the naval shipwreck at Point Honda, Calif. (1923), and U.S. Army officer James T. Watson, concerning judge advocate cases. Correspondents include Willard H. Brownson, Silas Casey, George Dewey, David Glasgow Farragut, William T. Meredith, David D. Porter, and Theodore Roosevelt.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Division.
Forms part of: Naval Historical Foundation collection.
Keywords: Brownson, Willard H. -- 1845-1935 -- Correspondence; Casey, Silas, -- 1841-1913 -- Correspondence; Dewey, George, -- 1837-1917 -- Correspondence; Chandler, William E. -- 1835-1917.; Edward -- VII, -- King of Great Britain, -- 1841-1910.; Farragut, David Glasgow, -- 1801-1870 -- Correspondence; Meredith, William T. -- Correspondence; Porter, David D. -- 1813-1891 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Watson family -- Correspondence; United States. -- Navy. -- Asiatic Squadron; United States. -- Navy. -- European Station; New York Naval Shipyard; Wyoming (Sloop of war); Mobile Bay, Battle of, Ala., 1864.; Navy-yards and naval stations -- New York (State) -- New York; Shipwrecks -- California -- Honda, Point; Alabama -- History -- Civil War, 1861-1865.; Chalmette (La.) -- History; Fort Jackson (La.) -- History -- Siege, 1862.; Fort Saint Philip (La.) -- History; Louisiana -- History -- Civil War, 1861-1865.; Mississippi -- History -- Civil War, 1861-1865; New Orleans (La.) -- History -- Capture, 1862.; United States -- History -- Civil War, 1861-1865.; Vicksburg (Miss.) -- History; Army officers; Naval officers